Optic-flow selective cortical sensory regions associated with self-reported states of vection - Uesaki, Maiko; Ashida, Hiroshi (Frontiers in Psychology, 2015)
Optic flow is one of the most important visual cues to the estimation of self-motion. It has repeatedly been demonstrated that a cortical network including visual, multisensory and vestibular areas is implicated in processing optic flow; namely, visual areas middle temporal cortex (MT+), V6; multisensory areas ventral intra-parietal area (VIP), cingulate sulcus visual area (CSv), precuneus motion area (PcM); and vestibular areas parieto-insular vestibular cortex (PIVC) and putative area 2v (p2v). However, few studies have investigated the roles of and interaction between the optic-flow selective sensory areas within the context of self-motion perception. When visual information (i.e. optic flow) is the sole cue to computing self-motion parameters, the discrepancy amongst the sensory signals may induce an illusion of self-motion referred to as ‘vection’. This study aimed to identify optic-flow selective sensory areas that are involved in the processing of visual cues to self-motion, by introducing vection as an index and assessing activation in which of those areas reflect vection, using functional magnetic resonance imaging (fMRI). The results showed that activity in visual areas MT+ and V6, multisensory area VIP and vestibular area PIVC was significantly greater while participants were experiencing vection, as compared to when they were experiencing no vection, which may indicate that the activation in MT+, V6, VIP and PIVC reflects vection. The results also place VIP in a good position to integrate visual cues related to self-motion and vestibular information.